From Classroom to Workplace: Contributions of Pursuing Graduate Studies on Personal and Professional Development - Cayabas, Johnny Pawid (International Journal of Learning, Teaching and Educational Research, 2025)
The knowledge and skills gained in the classroom play a vital role in developing the professional abilities of graduate students as they enter the workforce. Using a qualitative approach, this study examined the experiences of seven selected graduates of the Master of Public Administration program at Mountain Province State University. Relying on interview narratives as the primary basis for discussion, this study found that pursuing graduate studies significantly contributes to participants’ personal and professional growth. Personal development aspects include career advancement, increased confidence, critical thinking and problem-solving skills, and communication skills. Professional development encompasses enhanced leadership abilities, improved policy analysis and development skills, expanded public sector expertise, proficiency in resource management, better decision making, and crisis management capabilities. Based on these findings, the study recommends the following: updating the curriculum to adapt to political and administrative disruptions; offering workshops and training sessions to foster skill development for real-world challenges; improving faculty expertise and classroom environments by providing conducive learning spaces; forming research collaborations with government and research institutions; promoting mentorship programs; engaging with alumni; and creating networking opportunities. https://doi.org/10.26803/ijlter.24.12.39